Analisis Konsep Fisika Pada Teknologi Rotary Dryer Dan Mesin Combine Untuk Hasil Pertanian - Ramadani, Gischa Novi; Wulansari, Rania; Wicaksono, Haikal; Sudarti, Sudarti; Mahmudi, Kendid (Jurnal Ilmiah Wahana Pendidikan, 2025)
The processing of rice and corn crops today relies heavily on the utilisation of physical principles in the use of modern machinery. Rotary dryers dry grain and corn kernels by relying on heat and mass transfer, mainly through convection and conduction processes. Factors such as air temperature, airflow speed, drum rotation, as well as the thermal properties of the material being dried, greatly affect the speed of water evaporation and the quality of the final product. Meanwhile, combine harvesters integrate various stages of work-from cutting, threshing, separating, to cleaning-by utilising the concepts of mechanical force, impulse, friction, and centrifugal force. The effectiveness and efficiency of this machine depends on the settings of drum speed, cutting angle, forces acting on the crop, and vibration frequency in the separation system. Understanding the fundamentals of physics in this technology is key to designing a more efficient and energy-efficient machine. With proper application of the principles, the productivity and quality of rice and maize crops can be improved, especially in facing the challenges of tropical climate in the main agricultural areas. An in-depth understanding of the principles of physics is instrumental in improving the efficiency and quality of rice and corn yields after harvest. Through the development of sustainable rotary dryer and combine harvester technologies, it is expected that the productivity of the agricultural sector can increase significantly, while minimising the negative impacts of erratic tropical climate conditions. With the application of this physics-based technology, the agricultural sector can achieve more optimal results, reduce post-harvest losses, and utilise resources more effectively and sustainably.